Mobilized marketing : driving sales, engagement, and loyalty through mobile marketing - Hasen, Jeff, 1958- (Hoboken, N.J. : Wiley, 2012)
'Integrate your mobile marketing program and take your brand to the next levelMobile marketing is finally entering the forefront of the marketing realm as megabrands roll out million-dollar budgets and small businesses have turned to the channel for its affordability, measurability, and repeatable successes in producing sales and driving engagement and loyalty. Through insights from bold industry visionaries and fellow mobile pioneers, Mobilized Marketing takes readers through campaigns worth repeating and others that are not. Learn the many roads that marketers can take and the proven strategies and tactics that move products and build loyalty through the consumer's most personal device.With examples from the more than 130,000 campaigns developed by mobile marketing leader Hipcricket, Mobilized Marketing breaks down how brands of all sizes have performed in their mobile efforts--why some have failed and how others bravely turned to mobile. Demonstrates how to integrate mobile into marketing programs and how to effectively measure it Explains how to make your existing marketing spends work harder Delivers step-by-step instructions on how to optimize campaigns in real-time Shows how to determine which mobile tactics are keepers and which are not It's time to mobilize your marketing programs and drive your profits to new heights'--
Includes index.
Keywords: Telemarketing; Mobile commerce; Internet marketing; Cell phone advertising; BUSINESS & ECONOMICS / Marketing / General